(untitled) (Medical Forum Monthly, 2024)
Objective: The study is planned to find out the frequency of various skin lesions in OPD of a district level hospital. Study Design: Retrospective / Descriptive study. Place and duration of study: The study was conducted in OPD of Department of Dermatology, Civil Hospital, Hyderabad form 1st January to 31st December, 2016. Material & Method: The study included 801 cases attending the Dermatology OPD of Civil Hospital, Hyderabad. The cases were divided into A, B & C Groups; Group A comprised of children, Group B adults and group C old age patients. Each group comprised 267 patients. This study was mainly based on clinical examination but in some cases laboratory help from LUMHS research laboratory was taken. Results: In Children Infestations were highest (37.45%), next were cases of bacterial infections (24.34%), Fungal infections (19.10%), viral (11.23%) and atopic (7.86%). In Adults viral infections were highest (29.96%), next were cases of infestations (22.47%), fungal (20.22%), atopic (17.97%) & bacterial infections (9.36%). In old age patients Fungal infections (48.69%) were highest, next were cases of viral (17.60%), bacterial infections (14.98%), infestations (11.23% )and atopic (7.49%). Conclusion: The skin lesions are very common in our practice. To reduce the spread of all sorts of infections and infestations among the population it is necessary to follow preventive measures. Public at large must be made aware of simple measures like avoidance of sharing of clothing, sports items, towels or bed sheet. Washing of clothes should be done with hot water. Fungicidal soap should be used in suspected exposure to ring worms. Barefoot walk should be avoided.